The efficacy of conventional postharvest treatments on Rosmarinus officinalis shelf life - Stefanou, Constantinos (My University, 2022)
Rosmarinus officinalis is a well-known medicinal plant, used in the food industry as herb or a natural preservative, however, limited information for its postharvest preservation is available. This study aims to find a natural way of preserving fresh rosemary in order to increase shelf or/and storage life. Rosemary batched were dipped in distilled water (control), H2O2 10 g L-1 or 20 g L-1 for 1 min, ethanol 30% or ethanol 50% for 10 s or subjected to low O2 for 30 min or for 1 h. Quality related parameters were observed during or at the 10th day of storage at 6 oC, including sensory evaluation, respiration rate, phenols, ascorbic acid, antioxidants, flavonoids and natural microflora. Application of ethanol 50% increased weight loss on the 10th day, whereas, on the 2nd day, application of low O2 (30 min or 1 h) had higher weight loss rate in comparison to the other treatments. Respiration rate increased with the ethanol 30% application in comparison with the rest of the treatments (except low O2 for 1 h). Moreover, ethanol 50% had the lowest respiration rate from all seven treatments on the 10th day of storage. Total variable counts of rosemary were significantly lower with the 30% or 50% ethanol application compared to H2O2 10 g L-1, on the 10th day of storage. Furthermore, ethanol (30% and 50%) application decreased yeasts and molds in comparison with the other treatments. In addition, the application of low O2 30 min treatment led to the most marketable and aromatic product after the control. Overall, the low O2 30 min treatment appears to be the best postharvest method for the preservation of fresh rosemary followed by H2O2 10 g L-1. Further investigation for postharvest methods in herbs could include ozone exposure, high CO2, temperature and use of essential oils.
Keywords: Rosemary; Postharvest quality; Preservation; Hydrogen peroxide; Ethanol; Low oxygen (hypoxia)